Bioactive coumarin-derivative esculetin decreases hepatic stellate cell activation via induction of cellular senescence via the PI3K-Akt-GSK3β pathway. (December 2022) - Zhang, Mengfan; Damba, Turtushikh; Wu, Zongmei; Serna-Salas, Sandra; Buist-Homan, Manon; Faber, Klaas Nico; Moshage, Han
Abstract: Background: Activation of hepatic stellate cells (HSC) leads to initiation and progression of hepatic fibrosis. HSC senescence is inversely correlated with HSC proliferation and activation. Therefore, induction of HSC senescence may be a strategy to treat hepatic fibrosis. Coumarin-derivatives like esculetin have been suggested to inhibit proliferation of fibrogenic cells. Therefore, in this study we aimed to investigate the effect of esculetin on HSC activation and senescence . Methods: Primary rat HSC were used in all experiments. Real-time cell analyzer and BrdU incorporation assay were used to determine HSC proliferation. Gene expression of the senescence-associated genes Cdkn1a (p21), P53, activation markers Acta2, Col1a1 and quiescence markers Pparg and Lrat were measured by RT-qPCR. Senescence associated β-Galactosidase (SA-β-Gal) staining was used to identify senescent HSC. Results: Our results demonstrate that esculetin increased markers of senescence and decreased proliferation and activation markers in HSC. Protein expression of P21 Cip1, accompanied by phosphorylation of Ser473 Akt and Ser9 GSK3β was increased by esculetin. The effect of esculetin was dependent on PI3K-Akt signaling. Conclusion: We conclude that esculetin induces HSC senescence and reverses the activated phenotype of HSC. The induction of senescence depends on PI3K-Akt-GSK3β signaling. Esculetin could be a potential therapeutic drug for the treatment of hepatic fibrosis by inducing stellate cell senescence.